CAN ISLAMIC MICROFINANCE ALLEVIATES POVERTY IN INDONESIA? AN INVESTIGATION FROM THE PERSPECTIVE OF THE MICROFINANCE INSTITUTIONS - Adhitya Ginanjar; Salina Kassim (Bank Indonesia, 2020)
This study examines the poverty alleviation efforts undertaken by the Islamic microfinance institutions (IMFIs) in Indonesia. We focused on the role played by the IMFIs in view of their direct involvements in the process of dealing with the borrowers, and their better understanding about the financial inclusion agenda as well as the financial guidelines and regulations issued by the relevant authorities. In methodology, a total of 34 managers of Baitul Maal wat Tamwil (BMTs) were taken as respondents from the Jakarta, Bogor, Depok, Tangerang and Bekasi (JABODETABEK) areas. A two-step approach was adopted in arriving at enriching findings: first, a survey questionnaire was distributed to the respondents, and subsequently, an in-depth interview was conducted to outline data related to the model design. The findings of this study highlight specific dimensions to improve financial inclusion among the poor. Apart from providing important inputs for better decision-making for the BMTs to further enhance its role in poverty alleviation, this study suggests a variety of strategies to warrant success of poverty alleviation efforts by BMT.